A comparison of United Kingdom primary care data with other national data sources for monitoring the prevalence of smoking during pregnancy - Dhalwani, Nafeesa N.; Tata, Laila J.; Coleman, Tim; Fiaschi, Linda; Szatkowski, Lisa (Oxford University Press, 2014)
Background: We aimed to assess the potential usefulness of primary care data for estimating smoking prevalence in pregnancy by comparing the primary care data estimates with those obtained from other data sources. Methods: In The Health Improvement Network (THIN) primary care database we identified pregnant smokers using smoking information recorded during pregnancy. Where this information was missing, we used smoking information recorded prior to pregnancy. We compared annual smoking prevalence from 2000 to 2012 in THIN with measures from the Infant Feeding Survey (IFS), Smoking At Time of Delivery (SATOD), Child Health Systems Programme (CHSP) and Scottish Morbidity Record (SMR). Results: Smoking estimates from THIN data converged with estimates from other sources after 2004, though still do not agree completely. For example, in 2012 smoking prevalence at booking was 11.6% in THIN using data recorded only during pregnancy, compared to 19.6% in SMR data. However, the use of smoking data recorded up to 27 months before conception increased the THIN prevalence to 20.3%, improving the agreement. Conclusion: Under-recording of smoking status during pregnancy results in unreliable prevalence estimates from primary care data and needs improvement. However, the inclusion of pre-conception smoking records may increase the utility of primary care data.